2018
DOI: 10.1088/1742-6596/1049/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Simple Assembly Line Balancing Problem Type 1 (SALBP-1) with Machine and Worker Constraints

Abstract: Abstract-This paper presents a mathematical model for Simple Assembly Line Problem Type 1 (SALBP-1) with resource constraints; machine and worker. The existing model of SALBP-1 assumes that all the workstations have similar capability, while in reality the workstation has different capability because of limitation in term of machines and worker skills. The proposed model is aimed to mathematically represent the SALBP-1 with resource constraints. Besides that, three objective functions which to minimize number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results showed that the heuristics and lower bounds method could solve the problem well and was the most effective in this regard. The work carried out by Kamarudin et al (2018) [18] presented a mathematical model with resource constraints. The study found that the mathematical model could minimize the resources and decrease costs.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the heuristics and lower bounds method could solve the problem well and was the most effective in this regard. The work carried out by Kamarudin et al (2018) [18] presented a mathematical model with resource constraints. The study found that the mathematical model could minimize the resources and decrease costs.…”
Section: Introductionmentioning
confidence: 99%
“…In Type-E problems, the objective function is the efficiency of the assembly line. In Type-F problems the objective is to find a feasible balance between the number of workstations and cycle time which are both fixed [6], [7]. The above standard problem types can be further particularized to specific applications by customizing the mathematical formulation of the optimization problem.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…In [9], the authors solve a MMALBP addressing simultaneously the line balancing and sequencing problems, comparing the performances of two algorithms: the multi-objective particle swarm optimization (MOPSO) and the non-dominated sorting genetic algorithm (NSGA-II); results show that the latter has better performances. In [7], the authors address a SALBP-1 problem with resources constraints. Three different objective functions are taken into account: minimization of workstations, machines used and the number of multi-skilled workers.…”
Section: B Literature Reviewmentioning
confidence: 99%